Effects of N-acetylcysteine on Pulmonary Functions in Patients with Systemic Sclerosis: A Randomized Double Blind, Placebo Controlled Study - Mehrabi, Samrad; Moradi, Maryam M.; Khodamoradi, Zohre; Nazarinia, Mohammad A. (Current Rheumatology Reviews, 2020)
Background: Systemic sclerosis (SSc) is a systematic and rare autoimmune disease that affects many organs. N-acetylcysteine (NAC), thiol-containing compound, can act both as the precursor of reduced glutathione and direct scavenger of reactive oxygen species. Objective: We assessed the clinical effect of NAC on the pulmonary function test of patients with diffuse scleroderma. Methods: This study is a randomized double-blind clinical trial that was done on 25 patients with diffuse SSc without lung involvement on primary chest high-resolution computed tomography. Placebo was administered for 13 patients and 1200 milligram NAC for 12 patients. Body plethysmography parameters were assessed at the beginning of the study and after 24 weeks. Results: Patients in the two groups were matched in the basic demographic data like age, duration of disease, and modified Rodnan skin score. The analysis showed no significant differences in parameters of plethysmography between the two groups. After importing the data of 2 patients in the placebo-treated group, who developed interstitial lung disease, DLCO in the placebo-treated group was 90.69 ± 21.29 milliliter at the end of the study, which significantly decreased compared with the beginning of the study (102.30 ± 13.83 ml). Also, changes of DLCO between the two groups were significantly different. Conclusion: In this trial, the sensitivity of DLCO as the first marker in the evaluation of pulmonary function in patients with SSc was confirmed. On the other hand, NAC had no effect versus placebo in a period of 24 weeks.
Keywords: N-acetyl cysteine